Inváziós növények Magyarországon - Kazinczi, Gabriella; Pál-Fám, Ferenc; Naszer, Heider; Lukács, Helga (Acta Scientiarum Socialium, 2013)
Invasive alien plants in Hungary The rapid spreading of invasive alien plant species (IAS) mean a real threath both in natural and agro- ecosystems. These species endanger the ecological balance of natural communities and severely reduce the biological diversity. In the agricultural practice they cause considerable yield losses due to their favourable biological characteristics. To stop their future spreading the prevention method is the best against them. In the agriculture integrated protection methods are effective, envolving mechanical, physical, chemical, biological and agrotechnical ones. As a severe social consequence of the spreading of allergic invasive plants (most considerable is A. artemisiifolia in this respect) are: 1. decreased tourism in earlier frequented areas, like around the Lake Balaton, where the pollen concentration in the air is generally the highest in summer periods and 2. in the main pollen season the proportion of medicine costs and the persons on sick pay are high. Beside these allergy in this season considerably damages the life quality of the patients.
Keywords: invasive plants; weeds; natural ecosystems; agricultural ecosystems; biodiversity; pollen allergy